(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The research presents a statistical and analytical study of real and nomina Gross Domestic Product (GDP),and a detailed exploration of the sectoral structure of GDP in Syria during the twenty years [2000-2020]. It includes both the pre-war phase on Syria and the war phase. With the aim of identifying the most important economic sectors on which the Syrian economy relies، and which constituted its strengths during the stability phase and then were able to withstand during the war phase. These sectors could form a strong base for building a future strategy for the next stage in Syria. The results indicated that the GDP movement shifted from the productive sectors (industry and agriculture) before the crisis to the service sectors. It also showed the superiority of the industry and mining sector over various sectors، followed by agriculture and then trade. These results confirm the need to pay attention to the productive sectors، especially agriculture، to maintain the stability of the economic system in Syria.